PENERAPAN INTERNET OF THINGS UNTUK SISTEM PENDETEKSI DAN PENGENDALIAN ASAP DAN SUHU DALAM RUANGAN - Pratama, Farhan Abdi; Rifka , Silfia; Lifwarda, Lifwarda (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Clean air and comfortable temperature are important factors for the health and comfort of indoor occupants. Smoke, especially cigarette smoke, and high temperatures can reduce air quality and have a negative impact on health. This research aims to design and implement an Internet of Things (IoT)-based indoor smoke and temperature monitoring and control system. The system uses MQ2 sensor for smoke detection and DHT22 sensor for temperature measurement, controlled by ESP32 microcontroller connected via Wi-Fi. Sensor data is processed in real-time to automatically activate the exhaust fan and fan based on predetermined thresholds. In addition, the system provides manual control through a mobile application developed in MIT App Inventor, and data is stored in Google Sheets for historical monitoring. Test results show the system is can to accurately monitor smoke levels and temperature and control actuators both automatically and manually. Sensor data was successfully transmitted and stored in Google Sheets with minimal delay. This system provides an effective solution to improve air quality and space comfort using IoT technology.